The mushrooming of alcohol establishments: a case study of greenwell matongo, Windhoek, Namibia - Hasheela, Miriam Winnie; Ananias, Janetta Agnes; Schenck, Catherine (Penerbit Universiti Kebangsaan Malaysia, 2020)
This qualitative paper aimed at exploring the mushrooming of alcohol establishments in a residential area and potential effects on a community in Namibia. A case study design was applied to explore experiences from 18 participants through in-depth interviews. The purposive sampling method was used to draw participants from various sectors in the community such as self-employed and unemployed persons, shebeen owners, general community members (community councillor, a school teacher, and a police officer), people working at shebeens, and residents who have signed the shebeen consent letter. Data were analyzed employing the thematic data analysis method. The collected data were themed into five major themes, namely economic effects, environmental effects, increase in alcohol consumption, poor parenting and an increase in crime. The paper noted that there is a high density of alcohol outlets which is mostly associated with social, economic and environmental effects. The study concluded that too many alcohol establishments in one community increase the chances of social ills compared to a community where alcohol outlets are fewer. This study recommends policy on a stricter monitoring system of alcohol outlets, especially in low-income communities.